Is the effect worth the risk? - The most common complaints during oral isotretinoin anti-acne therapy and controversies around its adverse effects - Drozd, Małgorzata; Marzęda, Magdalena; Blicharz, Agnieszka; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Acne vulgaris, the most common skin disease, causes medical, esthetic and psychosocial problems. Isotretinoin, the vitamin A-derivative, has been the most effective treatment for acne vulgaris. It provides significant improvement and long-term remission. However, it leads to multiple side effects. The aim of our study was to evaluate the prevalence of adverse effects in patients treated with isotretinoin and analyze the most commonly reported symptoms. Material and methods: The study was conducted using original survey questionnaire addressed to members of Polish group of patients treated with isotretinoin. 196 responds were collected and confronted with current PubMed publications. Results: The most common mucocutaneous side effects, such as dry lip, dryness of the mucous membranes, xerodermia and dryness of the conjunctiva occurred in 92,6%, 73,5%, 66,8% and 66,3% of respondents, respectively. Both, tiredness and back pain were reported by 70,4% of respondents; myalgia - 55,1%, arthalgia - 32,1% and stiffness of joints - 26,0%. Mood change occurred in 54,6%, hair loss in 50,0%, gastrointestinal symptoms, such as abdominal pain and diarrhea – in 15,8% and 10,7%. Conclusions: All of the most common isotretinoin side effects are usually mild and dose-dependent. However, their prevalence is very high. Isotretinoin’s association to depression and suicidality remains unclear. In spite of the previous data, the risk of inflammatory bowel disease is probably not increased in patients isotretinoin exposed. However, more studies are necessary.